Dignity in dying - Dzierżanowski, Tomasz; Binnebesel, Józef (Medycyna Paliatywna/Palliative Medicine, 2019)
Dignity is a fundamental human attribute; it is natural, unconditional, and inherent. It is protected by law, especially in ill and dying persons. The conditions of dying in dignity may be grouped into four domains: (S) acceptable level of Suffering, (A) benevolent Accompanying, (R) Responsibility for one’s own life and awareness of dying, and the (M) Meaning of life, suffering, dying, and death. Supporting in these four domains realises the postulate of a holistic approach to the ill, suffering, or dying person, and the proposed order seems meaningful because it results from the hierarchy of human needs.